Xiaochaihutang Improves the Cortical Astrocyte Edema in Thioacetamide-Induced Rat Acute Hepatic Encephalopathy by Activating NRF2 Pathway - Jia, Weiyi; Liu, Jiajia; Hu, Rui; Hu, Anling; Tang, Weiwei; Li, Lijuan; Li, Jin (Frontiers in Pharmacology, 2020)
Oxidative stress induced by high ammonia, which lead to astrocyte edema, is the key to acute hepatic encephalopathy (AHE). Nuclear factor erythroid 2-related factor 2 (NRF2) has been implicated in oxidative stress, but the mechanism of NRF2 against ammonia-induced astrocytes edema has not been fully studied. We confirmed that NRF2 pathway is related to brain edema caused by AHE, and found that Xiaochaihutang (XCHT) could effectively activate NRF2 pathway to treat AHE. The model of AHE was established with thioacetamide (TAA) in rats. Rat behaviors were observed, brain water content, blood ammonia levels, glutamine synthetase (GS), malondialdehyde (MDA) and total superoxide dismutase (T-SOD) were determined after XCHT treatment. Furthermore, the expression of NRF2 pathway proteins and mRNA, glial fibrillary acidic protein (GFAP) and aquaporins 4 (AQP4) were examined. In order to determine whether XCHT has direct effect on cerebral edema caused by high ammonia, so we examined the effect of XCHT compound serum on cortical astrocytes in the presence of ammonia through observation and immunofluorescence (IF). Results showed that TAA caused AHE, changed the behavior of the rats, increased brain water content, blood ammonia levels, GS and MDA content, also decreased T-SOD, but these symptoms were improved by treatment with XCHT. XCHT protected brain edema by activating NRF2 pathway and increasing the expression of downstream proteins and genes. Astrocytes treated with 5 mM * Correspondence author.E-mail address: lijin010502@163.com Weiyi Jia and Jiajia Liu made equal contributions to this work. ammonia also showed a decrease in the AQP4 protein expression but reduced in XCHT compound serum and ammonia-induced cell edema group. This study demonstrates that NRF2 pathway involves in the brain edema in AHE, and taking XCHT may represent a useful approach for the treatment of AHE.